Fifty years of the International Court of Justice : essays in honour of Sir Robert Jennings essays in honour of Sir Robert Jennings - Jennings, R. Y. (Robert Yewdall), 1913-2004.; Lowe, A. V. (Alan Vaughan); Fitzmaurice, M. ([Cambridge] : Grotius Publications ; Cambridge ; New York : Cambridge University Press, 1996)
To mark the fiftieth anniversary of the International Court of Justice, a distinguished group of international judges, practitioners and academics has undertaken a major review of its work. The chapters discuss the main areas of substantive law with which the Court has been concerned, and the more significant aspects of its practice and procedure in dealing with cases before it. It discusses the role of the Court in the international legal order and its relationship with the political organs of the United Nations. The thirty-three chapters are presented under five headings: the Court; the sources and evidence of international law; substance of international law; procedural aspects of the Court's work; the Court and the United Nations. It has been prepared in honour of Sir Robert Jennings, judge and sometime President of the Court.
Sir Robert Yewdall Jennings / Vaughan Lowe -- List of publications of Sir Robert Jennings -- 1. The International Court as a world court / Georges Abi-Saab -- 2. The International Court and the voice of justice / Philip Allott -- 3. The London Committee and the statute of the International Court of Justice / Geoffrey Marston -- 4. The International Court of Justice and the sources of international law / Maurice Mendelson -- 5. Municipal law reasoning in international law / M. Shahabuddeen -- 6. Estoppel and acquiescence / Ian Sinclair -- 7. L'Equite dans la jurisprudence de la Cour Internationale de Justice / Prosper Weil -- 8. The International Court of Justice and the law of treaties / E.W. Vierdag -- 9. International 'soft law': a contemporary assessment / Francesco Francioni -- 10. The Court's role in relation to international organizations / D.W. Bowett.
"List of publications of Sir Robert Jennings": p. xxv-xxviii.
Includes bibliographical references and index.
Keywords: Jennings, Robert Yewdall; Jennings, Robert Yewdall; International Court of Justice; Cour internationale de justice; Cour internationale de justice; ICJ; CIJ; International courts; Bibliographie